Usability and Preliminary Learning Outcomes of a Visual Novel Game on the Circulatory System for Grade V Students - Julius Bata; Pauelina Charmelita (Jurnal Pendidikan Terapan, 2026)
Purpose: This study reports the classroom implementation and student-perceived usability of SIRKULASIKU, a visual novel game developed with the ADDIE model for fifth-grade IPAS (natural science) learning on the human circulatory system, and examines preliminary learning outcomes as indicative evidence of its instructional potential. Methods: A descriptive quantitative design with a one-group pretest–posttest component was used. Eighteen fifth-grade students (aged 10–11) from a private elementary school in Bekasi Regency participated in a single 70-minute session. Usability was measured with the Indonesian adaptation of the System Usability Scale (SUS); learning outcomes were measured with a 10-item multiple-choice test analysed using N-gain and the Wilcoxon signed-rank test. Findings: The mean SUS score was 73.75 (SD = 15.58), within the Good rating, with acceptable internal consistency (Cronbach’s α = 0.78), and learnability and ease of use as the strongest items. As preliminary single-group evidence, scores rose from 66.11 at pre-test to 90.56 at post-test, giving a mean N-gain of 0.725 (Wilcoxon W⁺ = 153.0, p < 0.001; effect size r = 0.85). An exploratory analysis found no significant link between usability and learning gain (Spearman’s ρ = 0.22, p = 0.37). Research Implications: The results offer preliminary, non-causal indications that a simple narrative-driven visual novel can support elementary science learning, and they suggest concrete design refinements, including an embedded tutorial and optional voice narration. Two measurement limitations should be acknowledged: the reliability and item characteristics of the knowledge test could not be assessed because item-level responses were not retained, and the SUS, which was developed for adult populations, may carry interpretive bias when used with children. Originality: This study advances the SIRKULASIKU project from expert-validated design to authentic classroom implementation, and provides a joint evaluations of usability and preliminary learning outcomes for a visual novel on the human circulatory system at the elementary level, an underexamined pairing in Indonesian IPAS research, where usability is rarely treated as a precondition for instructional value.